Penerapan Metode Technology Acceptance Model Untuk Mengetahui Tingkat Penerimaan Pengguna Aplikasi Vidio - Ramadhan, Kumara Aditya; Meiriza, Allsela; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Vidio is a Subscription video-on-demand (SVOD) platform offering video streaming services. Based on reviews of the Vidio application, it is known that many negative and low reviews related to the services provided have reduced in satisfaction and user acceptance. The aim of this study is to ascertain the extent of user acceptance by measuring the correlation between several variables. The approach to be utilized is Technology Acceptance Model by measuring the variables of perceived ease of use, perceived usefulness, behavioral intention to use, attitude towards using, and actual use with hypothesis test. The research was conducted on 100 Palembang city residents. Based on this research, there is a very strong positive correlation relationship between attitude towards using and behavioural intention to use. In addition, there is a strong positive correlation between the perceived usefulness variable and other variables except actual use. Overall from the results obtained, in the acceptance of users of the Vidio application, variable exhibits a notable and positive impact on this research.